2005
DOI: 10.1111/j.1464-410x.2005.05617.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography vs magnetic resonance imaging for defining the upper limit of tumour thrombus in renal cell carcinoma: a study and review

Abstract: undergoing surgery had pathological confirmation of tumour thrombus extent. All images were analysed originally, then reanalysed by two independent radiologists, an experienced urologist and a urological trainee unaware of the original reports and other imaging results, with a final determination on tumour thrombus level by consensus. RESULTSThe multidetector CT results were completely accurate when compared with surgical specimens and were in agreement with MRI on all but one occasion, where MRI determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 35 publications
(72 reference statements)
1
50
0
4
Order By: Relevance
“…Recently published study by Lawrentschuk et al also showed the complete accuracy of MDCT in detection of the upper extent of the tumor thrombus compared with surgical report. In that study, MDCT was accurate in all the eight cases [43].…”
Section: Discussionmentioning
confidence: 95%
“…Recently published study by Lawrentschuk et al also showed the complete accuracy of MDCT in detection of the upper extent of the tumor thrombus compared with surgical report. In that study, MDCT was accurate in all the eight cases [43].…”
Section: Discussionmentioning
confidence: 95%
“…Para ello puede ser útil la utilización de la ecografía-doppler, ecografía transesofágica o la resonancia nuclear magnética con gadolinio 24 , siendo útil el TAC para el diagnós-tico inicial; de entre estas pruebas diagnósticas se ha considerado la RNM como la más sensible y específica para la valoración de la presencia y extensión del trombo en los vasos representando el gold standard 26 . La extensión craneal del tumor fue definida por Neves y Zincke 27 ; se pueden establecer cuatro niveles: nivel I, renal; nivel II, infrahepático; nivel III, retrohepático; nivel IV, atrial.…”
Section: Discussionunclassified
“…Identifying the extent of IVC involvement is crucial for staging & planning. Although the extent of IVC thrombus can be identified by abdominal sonography & computed tomography, the sensitivity of MRI is superior to these techniques (96-100%) & is now the gold standard for assessing the level of thrombus [21,22]. Currently MRIscan is the Gold Standard for delineating the level & extent of tumor thrombi in the IVC & staging of RCC with a Sensitivity of 96-100%.…”
Section: Level Of Thrombusmentioning
confidence: 99%
“…Currently MRIscan is the Gold Standard for delineating the level & extent of tumor thrombi in the IVC & staging of RCC with a Sensitivity of 96-100%. It may even rule out caval wall invasion so that exact surgical procedure can be planned [21,22]. Infrahepatic thrombi were present in about 58% of patients & retro hepatic & suprahepatic in about 28% & 14% respectively.…”
Section: Level Of Thrombusmentioning
confidence: 99%